Pengaruh Pengadaan Spare Part terhadap Kelancaran Operasional Kapal-Kapal Milik PT. Pelayaran Andalas Bahtera Baruna - Endia Rahman; Santun Irawan; Stevian Geerbel Adrianes Rakka (KALAO'S MARITIME JOURNAL, 2025)
This study also demonstrates the importance of coordination between the engineering, nautical, and logistics departments in ensuring a smooth spare part procurement process. Each part of the process, from ordering to delivery, has its own mechanisms that must be adhered to to ensure smooth vessel operations. The ordering process begins with the identification of spare part requirements submitted by ship staff, which are then forwarded to the relevant departments for evaluation and approval. After the evaluation process, a purchase order is created and sent to the selected supplier. Despite these well-established procedures, challenges arise related to timely delivery, which can sometimes impact vessel operations. Another major obstacle is issues arising from inaccurate implementation of SOPs in handling procurement. Several deficiencies in the implementation of standard operating procedures (SOPs) cause delays in the procurement process, impacting vessel operations. To address these challenges, the company is conducting more thorough planning for ship spare part requirements by ensuring that all procurement follows established SOPs. Furthermore, vessels are also required to provide regular feedback to the company regarding their required spare part requirements. In this way, the company is expected to minimize delays and ensure that spare parts procurement can be carried out efficiently and on time, which will ultimately support the smooth operation of the ship as a whole. Furthermore, the company is also striving to improve relationships with suppliers by conducting more intensive communication and ensuring that all suppliers understand the quality standards and expected delivery timeliness. These efforts aim to reduce the likelihood of delays and ensure the availability of needed spare parts.